‘Long journey to shelter’: a study protocol: a prospective longitudinal analysis of mental health and its determinants, exposure to violence and subjective experiences of the migration process among adolescent and young adult migrants in Sweden - Amal R Khanolkar; Erica Mattelin; Frida Fröberg; Linda Jonsson; Laura Korhonen (BMJ Open)
Introduction According to the UN Refugee Agency (UNHCR), around 40% of the 79.5 million forcibly displaced persons in the end of the year 2019 were children. Exposure to violence and mental health problems such as posttraumatic stress disorder are frequently reported among migrant children, but there is a knowledge gap in our understanding of the complex longitudinal interplay between individual, social and societal risk and resilience factors that impact mental health and well-being, quality of life and ability to function and adapt. There is also an urgent societal need to facilitate interdisciplinary and intersectoral collaborative efforts to develop effective methods to prevent, detect and respond to the needs of the migrants. This project will study adolescent and young adult migrants in Sweden using multiple methods such as quantitative analysis of data from a prospective cohort study and qualitative analysis of data gathered from teller-focused interviews. The aim is to understand how different factors impact mental health and integration into the Swedish society. Furthermore, individual experiences related to the migration process and exposure to violence will be studied in detail.Methods and analysis Study participants will include 490 migrants aged 12–25 years recruited through social services, healthcare, social media and the civil society. A subsample of adolescents (n=160) will be re-interviewed after 1 year. Data are collected using structured and semi-structured interviews along with saliva and hair sampling. Measures include sociodemographic data, longitudinal data on mental health and its determinants, including genotypes and stress-hormone levels, access to healthcare and the process of migration, including settlement in Sweden.Ethics and dissemination The Regional Ethics Board of Linköping (2018/292-31 and 2018/504-32) and the National Ethics Board (2019–05473,2020–00949 and 2021-03001) have approved the study. Results will be made available to participants, their caregivers, professionals working with migrants, researchers and the funders.